ASSOCIATION BETWEEN RETINITIS PIGMENTOSA AND PRIMARY ANGLE-CLOSURE GLAUCOMA: A BIOMETRIC ANALYSIS (Cuestiones de Fisioterapia, 2020)
A type of inherited retinal disease, retinitis pigmentosa (RP), causes patients to lose night vision as they reach adolescence, lose peripheral vision in young adulthood, and finally lose central vision as they age. To determine whether a relationship exists between primary angle-closure glaucoma (PACG) and RP, a retrospective case-control study was conducted in PACG patients with and without concomitant RP. The anterior chamber depth (ACD) was measured using ultrasound biomicroscopy (UBM). The axial length (AL) and lens thickness (LT) of the lenses were measured with A-scan biometry. Analyses were conducted using propensity score matching and mixed linear regression models. During this study, 540 patients with CPACG and 268 patients with APACG were recruited. Twenty-four patients had chronic primary angle-closure glaucoma (CPACG) associated with RP, and twenty-two had acute primary angle-closure glaucoma (APACG) associated with RP. The ACDs, ALs, and relative lens positions (RLP) of patients with PACG associated with RP did not differ significantly from those of patients with PACG alone (P > 0.05); however, the LT of patients with APACG associated with RP was significantly higher than that of patients with APACG alone (P < 0.05). RP patients with PACG and CPACG had the same biometric parameter characteristics as RP patients without PACG. It is possible that RP and angle-closure glaucoma are related by coincidence.